Recent Repair Technology for Aero-Engine Blades - Tao, Wang; Huapeng, Ding; Jie, Tang; Hao, Wang (Recent Patents on Engineering, 2015)
Many aero-engine blades are long-term operated in harsh environments. Due to high temperature and pressure in operation, as well as many external impacts, blades may have various defects, such as erosion, distortion, wear, cracks and impact dents. In terms of prolonging the service lives of blades, repair is an inevitable choice since replacement is far more expensive. Along with the development of the advanced manufacturing technology (AMT), repairing technologies of blades, which have always mainly depended on the manual operation in the past several ten years, have been one hot research pot in the aircraft maintenance. The research emphasis is to improve the automation level of repairing process. The reconstruction of digital model of damaged blade, overlay welding and machining the welded excess are the three key technologies which influence the automation level of repairing. In this paper, the approaches, methods and methodologies used for the three technologies are reviewed as well as the comparisons between them are made. Meanwhile, the research directions are pointed out. The future research works should be emphasized on reconstructing the damaged tip independent of design model or unused blade, repairing the single-crystal blade with laser, repairing the blisk and improving the robot repairing system. Here, We also discussed few related patents.
Keywords: Aero-engine